Species composition and distribution of Echinodermata and Mollusca at Xuan Dai Bay, Phu Yen province - Trung, Hoàng Đình (Hue University Journal of Science: Natural Science, 2019)
The species composition of Echinodermata and Mollusca at Xuan Dai Bay, Phu Yen province, was determined in eight investigations and surveys during 2017–2018. Ninety-three species belonging to 5 classes, 18 orders, 38 families, 59 genera, and 2 phylums distributed in 8 sampling locations were identified. The Mollusca is greater with 74 species belonging to 44 genera, 26 families, 12 orders, and 2 classes; phylum Echinodermata has 19 species belonging to 14 genera, 12 families, 6 orders, and 2 classes. A new checklist adds 26 new species, 11 new genera, and 13 new families to the 2010 Macro-invertebrates checklist of Xuan Dai Bay. The species composition is high at Vung Chua (65 species), followed by Vung La (65 species), Xuan Yen (61 species), Xuan Dai (53 species), Xuan Thanh (51 species), Xuan Phuong and Xuan Phu with 47 species each, and Vung Chao with 44 species. Besides, the results point out that nine benthic animal species have primarily economic value; six species are listed in Vietnam’s Red Data Book (2007) and Decision 82/2008 issued by the Ministry of Agriculture & Rural Development.